Pengaruh Kinerja Pegawai Terhadap Kualitas Pelayanan Publik Di Kantor Dinas Tenaga Kerja Dan Transmigrasi Kabupaten Gowa - Islamiyah, Andi Nur; Alyas, Alyas; Parawu, Hafiz Elfiansyah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purpose of this study was to determine how the influence of performance variables that had by employees on the quality variable of public service at  the Labor Office and Transmigration  Gowa Regency. This study used quantitative research methods with descriptive research. Data analysis technique  used descriptive statistics with a simple regressive formula. Data described in the form of tables, pictures, frequency and flow of data with assistance SPSS. The  results of this study showed that there was an influence of Employee Performance Against the Quality of Service in the Ministry of Manpower and Transmigration office. Therefore, the hypothesis in the study was accepted because supported by the significance value. The results of  analysis data concluded that more good  employee performance meant more good the quality of public service. On the contrary the lower the performance of the employee meant the quality of public service was getting low. Keywords: influence, employee performance, quality of public service